2019
DOI: 10.7199/ped.oncall.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Medium Chain Acyl CoA Dehydrogenase (MCAD) Deficiency in an Indian Neonate

Abstract: prognosis is excellent for those who survive metabolic crisis period without brain damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…All patients are under treatment with a reduced episode of hypoglycemia following precautionary advice. The study by Singh et al and Mahale et al have demonstrated the diagnosis of FAODs by TMS [ 21 - 22 ]. Patients with SCAD and LCAD deficiency presented with metabolic encephalopathy with a seizure disorder and succumbed to acute encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…All patients are under treatment with a reduced episode of hypoglycemia following precautionary advice. The study by Singh et al and Mahale et al have demonstrated the diagnosis of FAODs by TMS [ 21 - 22 ]. Patients with SCAD and LCAD deficiency presented with metabolic encephalopathy with a seizure disorder and succumbed to acute encephalopathy.…”
Section: Discussionmentioning
confidence: 99%